Exploring the Impact of a Supportive Work Environment on Chinese L2 Teachers’ Emotions: A Partial Least Squares-SEM Approach - Yonghong Zeng; Jiaying Yu; Hanwei Wu; Wentao Liu (Behavioral Sciences, 2024)
Second language (L2) teachers’ emotions can influence their well-being and students’ performance. However, most of the existing studies have focused on the role of individual factors in affecting L2 teachers’ emotions, while leaving environmental factors underexplored. To fill this gap, this study aimed to examine how the four dimensions of a supportive work environment (SWE) (perceived climate, PC; supervisory relationship, SR; peer group interaction, PGI; and perceived organization support, POS) relate to L2 teachers’ emotions (enjoyment, anxiety, pride, and anger). A sample of 406 Chinese L2 teachers completed two valid scales to measure their SWE and emotions. The data were analyzed by Partial Least Squares-Structural Equation Modeling (SEM) using Smart PLS 3 software. The results showed that (1) PC, PGI, and POS had a positive and significant effect on enjoyment, while SR had no significant effect; (2) PGI and POS had a negative and significant effect on anxiety, while PC and SR had no significant effect; (3) PGI had a positive and significant effect on pride, while the other three dimensions had no significant effect; and (4) POS had a negative and significant effect on anger, while the other three dimensions had no significant effect. The study concludes with some implications for L2 teachers’ education.